Effect of COVID-19 Prevention Measures on Air Quality in Thailand - Jenjira Kaewrat; Rungruang Janta (Aerosol and Air Quality Research)
Abstract The coronavirus disease 2019 (COVID-19) has been a global pandemic since early 2020. In Thailand, the number of cases increased exponentially from the middle of March 2020. In response, Thailand’s government has imposed various pandemic prevention measures, such as a rigorous stay-at-home measure to reduce viral transmission between humans. Many human activities ceased, such as transportation, businesses, and services. This has been associated with reductions in air pollutant emissions. This study thus aimed to measure air quality in metropolitan, industrial, and suburban cities of in Thailand. Data on the hourly concentrations of six criteria pollutants were obtained from Thailand’s Pollution Control Department from five stations during three measurement periods: pre-COVID, early COVID, and working-from-home (WFH) periods. The results indicated that vehicle-emitted pollutants had significantly decreased during WFH periods. Moreover, the air quality of all city types ostensibly improved (50%–70%) because of reduced transportation in Thailand’s central and eastern provinces. However, results for Northern provinces were unclear because PM2.5 concentrations were still high during WFH period due to effects from open burning activity as well as meteorological condition.